2013
DOI: 10.1002/pmic.201200560
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of amino acid utilization in Phaeobacter inhibensDSM 17395

Abstract: Time-resolved utilization of multiple amino acids by Phaeobacter inhibens DSM 17395 was studied during growth with casamino acids. The 15 detected amino acids could be grouped according to depletion rate into four different categories, i.e. from rapid (category I) to nondepletion (category IV). Upon entry into stationary growth phase, amino acids of category I (e.g. glutamate) were (almost) completely depleted, while those of categories II (e.g. leucine) and III (e.g. serine) were further consumed at varying r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(51 citation statements)
references
References 42 publications
1
49
1
Order By: Relevance
“…Starting from a glycerol stock, 3 passages were conducted before six main cultures (250 ml) were inoculated with 2% [vol/vol] preculture (25). At half-maximal optical density (½ OD max ), 20 ml of each main culture was further incubated in 100-ml Erlenmeyer flasks (see Fig.…”
Section: Cultivationmentioning
confidence: 99%
See 3 more Smart Citations
“…Starting from a glycerol stock, 3 passages were conducted before six main cultures (250 ml) were inoculated with 2% [vol/vol] preculture (25). At half-maximal optical density (½ OD max ), 20 ml of each main culture was further incubated in 100-ml Erlenmeyer flasks (see Fig.…”
Section: Cultivationmentioning
confidence: 99%
“…Furthermore, after phase separation, 1 ml of the upper polar phase was transferred to a 2-ml reaction tube and was dried in a vacuum concentrator for gas chromatography (GC)-MS analysis. The two-step derivatization reaction was performed essentially as described previously (25). Intracellular metabolites were analyzed by GC-MS as described previously (26) using a Leco Pegasus 4D GCϫGC-TOF MS (Leco Instrumente, Mönchengladbach, Germany) operated in GC-TOF mode and equipped with an MPS 2 XL autosampler (Gerstel, Mülheim an der Ruhr, Germany).…”
Section: Cultivationmentioning
confidence: 99%
See 2 more Smart Citations
“…The production level decreased above a glucose concentration of 5% because of the osmotic pressure of high glucose concentrations on the host cells. Moreover, it has been reported that the protein abundance profile and metabolism of microorganisms change dramatically with the nutrient conditions and growth phases (38,39). Therefore, we speculate that the redox balance and overproduction of RhSMO in the host cells were affected by the carbon source and its concentration.…”
Section: Discussionmentioning
confidence: 97%